Modern and Islamic Models of Teaching Instructions and Assessment Strategies in learning Objectives and Outcomes:In the light of Seerahut Nabi ﷺ - Dr Farhana Mehmood; Zia ur Rehman (MEI, 2023)
Education is a resolute activity, being administered to achieve certain aims. Imparting education includes mediating knowledge and fostering skills and character traits. Formal education takes place in educational institutions. It is usually structured by curricular aims and objectives and the learning is supervised by an educator. Models of teaching instruction include the principles, methods, and tools used by educators to enable students to comprehend knowledge. These strategies are acquired partly based on the subject matter to be taught and partly on the nature of the learner. For an appropriate and efficient teaching method, it must consider the nature of the learner, the nature of the subject matter, and the type of learning it is supposed to bring about. This research paper aims to highlight the above-mentioned objectives and how evolution in teaching methods took place in the ancient, medieval, nineteen, and twentieth centuries. It will also be explained how the latest teaching strategies can be used to improve the quality of education in the higher education sector. It will also be discussed how different teaching methodologies like lecturing, demonstrating, collaborating, classroom discussions, debriefing, and classroom action research can play a pivotal role in upgrading the educational domain in universities. Furthermore, it will be elaborated in this paper that Islam has thrown much emphasis on education and provides different strategies of educational methods in the Holy Quran and Sunnah of Prophet Muhammad P.B.U.H which should be implemented to improve the quality of education and to achieve a state of the art capabilities. The Qualitative Archival Method will be used for the collection of data. Chicago Manual 2017 will opt for paper writing.